Eccentric Stenosis of the Carotid Artery Associated with Ipsilateral Cerebrovascular Events - Ohara, T.; Toyoda, K.; Otsubo, R.; Nagatsuka, K.; Kubota, Y.; Yasaka, M.; Naritomi, H.; Minematsu, K. (American Journal of Neuroradiology, 2008)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf